Screwdriver assaults and intracranial injuries. Issue 3 (1st May 2000) - Tutton, Matthew G; Chitnavis, Bhupal; Stell, Ian M
Abstract : Four patients with intracranial penetrating injuries from screwdrivers are presented. Two cases were fatal; the others were left with functional deficits. In two of the patients a penetrating injury was not suspected initially because the history was limited and the significance of the small entry wounds were not appreciated. Unless these wounds are carefully examined a penetrating injury is easily overlooked.